2005
DOI: 10.1136/adc.2005.087270
|View full text |Cite
|
Sign up to set email alerts
|

Diminished lung function, RSV infection, and respiratory morbidity in prematurely born infants

Abstract: Background: Diminished lung function appears to be a risk factor for respiratory syncytial virus (RSV) infection/bronchiolitis in term born infants. Aims: To determine if diminished lung function prior to neonatal unit discharge was associated with subsequent symptomatic RSV lower respiratory tract infection (LRTI) and respiratory morbidity in prematurely born infants. Methods: Of 39 infants in a tertiary neonatal intensive care unit (median gestational age 28 weeks, range 23-31), 20 had bronchopulmonary dyspl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 20 publications
0
33
1
4
Order By: Relevance
“…Several risk factors for a severe course of disease during RSV infection, including premature birth [1,4], have been identified. Two studies assessed the role of neonatal lung function in RSV bronchiolitis in prematurely born infants [4,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several risk factors for a severe course of disease during RSV infection, including premature birth [1,4], have been identified. Two studies assessed the role of neonatal lung function in RSV bronchiolitis in prematurely born infants [4,10].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies assessed the role of neonatal lung function in RSV bronchiolitis in prematurely born infants [4,10]. DRYSDALE et al [10] prospectively studied 159 premature born infants that were sampled at each episode of wheeze, cough or shortness of breath.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous genetic studies have demonstrated a significant association between the inherited polymorphisms in several immunological and surfactant protein genes and the incidence of severe viral infection and level of infection-related morbidity among preterm infants [50,51]. Also, pre-existing impairments in lung function have also been attributed to increased susceptibility to severe viral infection and infection-related morbidity among preterm infants, particularly during early life [5254]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…관지염의 중증도가 바이러스 [2][3][4][5] 및 아토피 소견과는 무관하 거나 방어적 효과를 나타내며 [18][19][20] 이미 존재하는 폐기능 감 소 15,21) 및 유전적 요인과 관련이 있다고 제시한다. Values are presented as no.…”
unclassified